2015
DOI: 10.1038/cdd.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated inflammation connects RAS-induced senescence to stem cell dysfunction and epidermal malignancy

Abstract: Aging is the single biggest risk factor for malignant transformation. Among the most common age-associated malignancies are non-melanoma skin cancers, comprising the most common types of human cancer. Here we show that mutant H-Ras activation in mouse epidermis, a frequent event in cutaneous squamous cell carcinoma (SCC), elicits a differential outcome in aged versus young mice. Whereas H-Ras activation in the young skin results in hyperplasia that is mainly accompanied by rapid hair growth, H-Ras activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 78 publications
1
31
0
1
Order By: Relevance
“…The accumulation of Ki-67-positive cells and prolonged hyperplasia in the aged epidermis during recovery from carcinogenic treatments has been reported (Golomb et al, 2015). It would be intriguing to observe skin carcinogenesis upon COL17 deficiency, as its relevance in colon and lung cancers has been described (Liu et al, 2016a, 2016b; Moilanen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of Ki-67-positive cells and prolonged hyperplasia in the aged epidermis during recovery from carcinogenic treatments has been reported (Golomb et al, 2015). It would be intriguing to observe skin carcinogenesis upon COL17 deficiency, as its relevance in colon and lung cancers has been described (Liu et al, 2016a, 2016b; Moilanen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of the results of such dysregulation is that the plasma concentrations of inflammatory proteins can increase with age in healthy individuals , including proinflammatory cytokines such as interleukin (IL)‐6, tumour necrosis factor alpha (TNF‐α) and monocyte chemoattractant protein‐1 (MCP‐1) . Therefore, their upregulation in advanced ageing underlies a low‐grade, chronic, systemic proinflammatory state correlated with age‐associated diseases such as diabetes and obesity .…”
Section: Endothelial Dysfunction and Ageing: The Role Of Nitric Oxidementioning
confidence: 99%
“…Further, a recent study demonstrated that activation of oncogenic Hras in the mouse epidermis has differential effects in young and old skin. Although young mice develop epidermal hyperplasia, old mice develop tumors consistent with SCC along with increased numbers of proinflammatory cytokines (Golomb et al, 2015). In a mouse model of cutaneous SCC, cancer-associated fibroblasts induce SASP-like inflammation, angiogenesis, and tumor growth through an NF-κB-mediated mechanism, reinforcing the links between the SASP and tumorigenesis in the skin (Erez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%